Diagnosis and analysis of two king-post trusses - Branco, Jorge M. (2008)
An accurate geometric and mechanical evaluation of two king-post trusses, based in grading results with data gathered from NDT as well as from mechanical evaluation, followed by full-scale tests were performed. The trusses were reassembled in laboratory and submitted to a series of cyclic tests under symmetric and asymmetric loading. Strengthening techniques evaluated in precedents research steps were used in a second phase of the carrying tests.